2002
DOI: 10.1159/000064545
|View full text |Cite
|
Sign up to set email alerts
|

Electron Spin Resonance Detection of UVA-Induced Free Radicals

Abstract: Free radicals generated during UV irradiation of human skin biopsies were measured with electron spin resonance spectroscopy by using spin traps. The generation of hydroxyl and lipid radicals in skin is mainly caused by the UVA part of the solar spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…Electron spin resonance (ESR) studies have shown that lipid alkyl and alkoxyl radicals can be generated in skin biopsies following UVA exposure (Jurkiewicz and Buettner, 1996;Herrling et al, 2002). From a different aspect, Packer and coworkers have shown that the cutaneous antioxidant defense system can be impaired by UVA irradiation (Fuchs et al, 1989;Thiele et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Electron spin resonance (ESR) studies have shown that lipid alkyl and alkoxyl radicals can be generated in skin biopsies following UVA exposure (Jurkiewicz and Buettner, 1996;Herrling et al, 2002). From a different aspect, Packer and coworkers have shown that the cutaneous antioxidant defense system can be impaired by UVA irradiation (Fuchs et al, 1989;Thiele et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Radical formation was investigated using UV irradiation, which is known to induce free radicals in the skin [29,30] . EPR measurements were performed before and after 3, 6 and 9 min of UV irradiation of the skin.…”
Section: Radical Formation Induced By Uv Irradiationmentioning
confidence: 99%
“…Electron paramagnetic resonance (EPR) spectroscopy can be used to measure radical formation in the skin ex vivo as well as in vivo . So far, most of the investigations applying irradiation have been performed ex vivo . Only very few measurements could be found on single volunteers in vivo , because the major problem is to conduct reproducible measurements before and after irradiation when an external irradiation source is used.…”
Section: Introductionmentioning
confidence: 99%